IEO Evaluation Report : IMF Involvement in International Trade Policy Issues. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2020)
This report updates the 2009 IEO evaluation of IMF Involvement in International Trade Policy Issues. Since then, the composition and structure of international trade have evolved, but trade has not regained its former dynamism. With increasing concern about potential winners and losers from trade, there has been a loss of political support for globalization, increasing trade tensions and protectionism, and the institutional framework supporting multilateral trade has come under heavy strain. The report concludes that overall the IMF deserves considerable credit for its active and timely response, playing a prominent role in championing commitment to an open, rules-based multilateral trading system. The Fund has largely implemented the recommendations of the 2009 evaluation and has strengthened and consolidated its trade policy analysis and advice, appropriately focusing on the key macroeconomic effects and associated risks of trade policy developments at the national and international levels. IMF advocacy on trade has been underpinned by a major expansion in the attention to trade policy issues in multilateral surveillance-and to some extent in bilateral surveillance-supported by high-quality research and analysis, building on the Fund's well-established modeling capacity. Looking forward, the Fund will need to sustain its current high level of advocacy and analysis on trade policy issues and consider how to increase the overall impact of this work. Key challenges include: contributing to foster a recommitment to trade policy cooperation; further attention to translating multilateral surveillance into bilateral policy advice; consolidating relations with partner institutions; and increased attention to rapidly developing trade policy issues. Across all these dimensions, care will be needed to ensure appropriate evenhandedness in trade policy surveillance across countries. A holistic review of the IMF's 'trade strategy' would help to guide trade policy work and the allocation of scarce resources among competing priorities.